Human Lacrimal Production Rates from Modified Schirmer-Tear Test. Issue 4 (April 2018) - Li, Songhao; Kim, Young Hyun; Li, Wing; Lin, Meng C.; Radke, Clayton J.
Abstract : SIGNIFICANCE: A simple methodology is presented to quantify basal tear production with a modified Schirmer-tear test. PURPOSE: We introduce a simple clinical procedure to measure quantitative basal tear-production flowrates, Q L, from a modified Schirmer-tear test (STT). METHODS: Eight healthy subjects aged at least 18 years underwent modified STTs on both eyes for two visits each. Schirmer strips were sheathed with transparent tape before insertion. Topical anesthetic minimized reflex tearing. Wetting lengths were measured every 30 s for 5 min; Q L was calculated from the linear slope of wetting length versus time. Determination of Q L requires mass–balance equations on the tear prism and Schirmer strip with strip imbibition kinetics obeying Darcy and Young–Laplace laws. RESULTS: Basal tear production rates varied from essentially 0 to about 2 μl/min. With some exceptions, right and left eyes showed similar tear production rates. CONCLUSIONS: By following the modified STT, Q L is established with minimal additional effort over a standard Schirmer test. We predict and observe four different subtypes of imbibition kinetics depending on how short or long the time is for first appearance of the wetting front and on how fast or slow is tear production. For slow lacrimal production rates, the standard 5-min wetting length does not correlate with basal tear production. Abstract : Supplemental digital content is available in the text.